Higher education and inequality. (3rd April 2018) - Brown, Roger
ABSTRACT: After climate change, rising economic inequality is the greatest challenge facing the advanced Western societies. Higher education has traditionally been seen as a means to greater equality through its role in promoting social mobility. But with increased marketisation higher education now not only reflects the forces making for greater inequality but even exacerbates them. This could be changed but it would require major shifts in higher education policy and practice of which there is currently little sign.